Exploration Of The Influence Of Entrepreneurial Competence And Capital Support On The Success Of Micro-Enterprises In The Local Crafts Sector In Bima City - Amen Muhtadir; Muhammd Rizkan; Khas Sukma Mulya (LPPM Sekolah Tinggi Ilmu Ekonomi 45 Mataram, 2026)
This study aims to analyze the influence of entrepreneurial competencies and capital support on the success of microenterprises in the local handicraft sector in Bima City. The success of microenterprises is a key indicator in boosting the local economy, particularly in sectors based on local potential. However, microentrepreneurs still face various challenges, such as low entrepreneurial competence and limited business capital, which can hinder business growth. Therefore, this study was conducted to determine the extent to which entrepreneurial competence and capital support contribute to the success of microenterprises.This study employs a quantitative approach using a survey method. The study population consists of micro-business operators in the local handicraft sector in Bima City, while the sample was determined using purposive sampling. Data collection was conducted through questionnaires, brief interviews, and documentation. Data analysis utilized multiple linear regression with the assistance of the Statistical Package for the Social Sciences (SPSS).The results indicate that entrepreneurial competence has a positive and significant effect on the success of microenterprises. Capital support also has a positive and significant effect on the success of microenterprises. Simultaneously, entrepreneurial competence and capital support have a significant effect on the success of microenterprises in the local handicraft sector in Bima City. These findings suggest.